Frequency of Urological Injuries in Obstetrical and Gynaecological Surgery at Tertiary Care Hospital - Mudassar Saeed Pansota, Mubasher Saeed Pansota, Shagufta Nazar, Hafiz Muhammad Tariq, Muhammad Shahzad Saleem, Mumtaz Rasool, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Due to the anatomical proximity of the urogenital organs, reproductive and obstetrical procedures have been intrinsically linked to urological damage. The connection of the genital and urine tracts anatomically and during embryologic development makes the urinary system particularly vulnerable to damage during surgical procedures in the female. Urinary bladder and ureter injuries are a common post-gynecological or obstetrical surgery complication. Objectives: To determine the frequency of urological injuries in obstetrical and gynaecological surgery. Materials & Methods: A total of 142 women who are undergoing obstetric and gynecologic surgeries, 25 to 55 years of age were included. Patients having urological injury from other than obstetric and gynecologic surgeries were excluded. In this study all patients were included who are fulfilling inclusion criteria undergoing obstetric (cessarean section) & gynaecologic (laprotomies & hysterectomies) were enrolled after taking written informed consent. Risk factors for urological injuries were assessed in terms of indication (risk for surgery), site of ureteric injury, location of bladder injury was noticed. Results: Age range in this study was from 25 to 55 years with mean age of 40.20 ± 6.92 years. Majority of the patients 77 (54.23%) were between 41 to 55 years of age. Mean duration of surgery was 62.16 ± 14.52 minutes. Mean time interval after surgery was 37.51 ± 13.89 hours. In this study, frequency of ureteral injury, urinary bladder injury and mixed injury in obstetrical and gynaecological surgery was found in 20 (14.08%), 14 (9.86%) and 07 (4.93%) patients. Conclusion: This study concluded that understanding pelvic anatomy, detailed dissection, and patience in challenging cases are the essential elements to predict and reduce damage. Keywords: obstetrical and gynaecological surgery, ureteric injury, bladder injury.